CONTEXTS AND CHALLENGES OF LI-FI TECHNOLOGY - Fontanelli Boaro, Renan Josemar; De Oliveira Dian, Mauricio (Revista Interface Tecnológica, 2025)
This article aims to analyze Light Fidelity (Li-Fi) technology, an emerging alternative to Wireless Fidelity (Wi-Fi) for wireless data transmission. Through a bibliographic review, the main aspects and challenges related to Li-Fi implementation were investigated, including its advantages, such as higher transmission speed and enhanced security in environments where radiofrequency use is restricted, like hospitals and aircraft. The research highlights the need for innovative technological solutions to meet the growing demand for efficient and secure connectivity. Although not yet widely commercialized, Li-Fi has significant potential to transform the wireless communication landscape, depending on investments for large-scale adoption.